Intravenous fosphenytoin therapy for the rescue of acute trigeminal neuralgia crisis in pre- and post-neurosurgical patients: a retrospective observational study - Shusaku Noro; Hideki Endo; Bunsho Asayama; Yuki Amano; Masahiro Okuma; Ryota Nomura; Kaori Honjo; Yoshinobu Seo; Hirohiko Nakamura (Frontiers in Neurology)
BackgroundThere is no established treatment for the acute exacerbation of trigeminal neuralgia. We aimed to investigate the efficacy and safety of intravenous fosphenytoin for this disease.MethodsWe conducted a retrospective observational study of data from 41 patients with trigeminal neuralgia who received intravenous fosphenytoin therapy. Fosphenytoin diluted with physiological saline was administered intravenously at a loading dose of 9.8–20.7 mg/kg or at a dose of 7.5–9.5 mg/kg when maintenance therapy was needed. Pain was evaluated using a numerical rating scale (NRS), assessed immediately before administration (baseline) and at 2, 12, and 24 h after administration.ResultsThe mean (± standard deviation) NRS score was 9.85 ± 0.69, 0.49 ± 1.47, 1.60 ± 2.19, and 3.46 ± 3.19 at baseline, 2, 12, and 24 h after administration, respectively (p < 0.001). Intravenous fosphenytoin therapy was effective for the acute exacerbation of trigeminal neuralgia regardless of whether it was administered during the perioperative period of microvascular decompression (MVD) or the type of drugs used concomitantly. Fosphenytoin was effective when re-administered (n = 14) or at a maintenance dose (n = 2). The adverse drug reactions observed were mild dizziness in six patients, abnormal auditory perception and thirst in three patients each, and somnolence, decreased SpO2, and drug eruption in one patient each, all of which were transient.ConclusionsIntravenous fosphenytoin therapy can immediately eliminate pain during acute exacerbation of trigeminal neuralgia and can be a useful therapeutic drug in emergency response or until elective treatment, such as MVD, is performed.